MENINGKATKAN KETERAMPILAN GURU MENANGANI BULLYING: METODE SUPPORT GROUP - , Andini Dwi Arumsari; , MG Adiyanti, Psi ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Bullying is often occurred at schools. One of the causes of bullying that happens at schools is the lack of teachersâs skill in overcoming bullying. Intervention conducted by teachers is one of the crucial predictors of bullying and has become the determinant factor in reducing the number of bullying cases at schools. One of the interventions that could be utilized is support group method which is applied by involving group support from the bullies and the bystanders who witnessed the bullying event, not blaming the bullying behaviors, and not labeling those who are involved in a bullying situation. The purpose of the study was to improve skill of teachers in overcoming bullying using support group method. The design of the study was quasi experimental research. Data analysis was conducted using quantitative analysis, using U Mann-Whitney test to analyze the result of skill (reported) and knowledge test as manipulation check, and using t-test to analyze skill (observed). Psychoeducation was given to teachers of a State Elementary School located in Surabaya. Result of knowledge test showed a very significant difference with Z=-4,267 and significance level of (p) 0,000 (p<0,01). Skill (reported) showed a very significant difference with Z=-4,285 and significance level of (p) 0,000 (p<0,01). Skill (observed) also showed a very significant difference with t=4,316 and significance level of (p) 0,000 (p<0,01).